Gaps in the Dynamics and Performance of the Psychiatric Care Deinstitutionalization - Iveta Vrabková PhD; Ivana Vaňková PhD; Kristýna Moškořová PhD (SAGE Publishing, 2023)
This study objective to verify the existence of gaps in the dynamics and performance of fulfillment of the deinstitutionalization of psychiatric care in the Czech Republic (CZ) and the Slovak Republic (SR) in the period between 2010 and 2020. The introduction of this the study is a search for expert knowledge in the field of deinstitutionalization of psychiatric care. The study uses the method of multi-criteria comparison of TOPSIS variants and a cluster analysis. The results 22 variants range from (ci 0.6716-0.2571) and confirm that there are large differences between CZ and SR in performance gaps (fulfillment) of deinstitutionalization goals. The SR variants are clearly better than the CZ variants, although during the years studied, the CZ variants are improving, and the size of the gap compared to the SR variants is decreasing. In the first year of the evaluated period (2010), the performance gap was 56% and in the last year (2020), the performance gap was only 31%. The conclusion of the study confirms that the measures associated with the deinstitutionalization of psychiatric care are linked to the time they were introduced and the overall implementation period of the reform.